The Innovation of English Learning Resources Utilizing Interactive Games Aimed at Elementary School Students in Desa Pasar X - Thereza Angie Grifin; Rani Amelia Sihite; Sabrina Wandani Hutabarat; Mesra Sinambela; Chairos Valentino Sibarani (Saniya Institute, 2024)
This study addresses the underutilization of effective learning media to enhance elementary school students' comprehension of English. The primary objective is to create interactive, game-based learning tools that enhance students' understanding of English vocabulary. The research specifically targets elementary school students in Pasar X Village, Kutalimbaru. Employing the Research and Development (R&D) methodology, the study follows the ADDIE model, which encompasses five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods included observation and pre-test and post-test assessments to measure students' understanding. The implementation of interactive games, such as board games and plasticine activities, demonstrated significant effectiveness. The post-test results indicated a notable improvement in student comprehension, rising from 69.5% in the pre-test to 80.25%, thereby confirming that these media enhance students' retention and engagement in English learning. The successful development of interactive, game-based learning media has significantly strengthened students' vocabulary knowledge, fostering a dynamic, enjoyable learning environment that encourages active participation and skill development.